Maternal Organic Selenium Supplementation Relieves Intestinal Endoplasmic Reticulum Stress in Piglets by Enhancing the Expression of Glutathione Peroxidase 4 and Selenoprotein S - Ding, Dajiang; Mou, Daolin; Zhu, Heng; Jiang, Xuemei; Che, Lianqiang; Fang, Zhengfeng; Xu, Shengyu; Lin, Yan; Zhuo, Yong; Li, Jian; Huang, Chao; Zou, Yuanfeng; et al. (Frontiers in Nutrition, 2022)
Endoplasmic reticulum (ER) stress, which can be induced by reactive oxygen species (ROS) and multiple factors, is associated with numerous intestinal diseases. The organic selenium source 2-hydroxy-4-methylselenobutanoic acid (HMSeBA), has been proved to decrease intestinal inflammation and autophagy by improving the expression of selenoproteins. However, it remains unclear whether HMSeBA could alleviate intestinal ER stress by decreasing excessive production of ROS products. This study was conducted to investigate the effect of maternal HMSeBA supplementation on the regulation of intestinal ER stress of their offspring and the regulatory mechanism. Sows were supplemented with HMSeBA during gestation and jejunal epithelial (IPEC-J2) cells were treatment with HMSeBA. Results showed that maternal HMSeBA supplementation significantly upregulated mRNA level of selenoprotein S (SELS) in the jejunum of newborn and weaned piglets compared with the control group, while decreased the gene expression and protein abundance of ER stress markers in the jejunum of LPS challenged weaned piglets. In addition, HMSeBA treatment significantly increased the expression of glutathione peroxidase 4 (GPX4) and SELS, while decreased ROS level and the expression of ER stress markers induced by hydrogen peroxide (H2O2) in IPEC-J2 cells. Furthermore, knockdown of GPX4 did not enhance the ERS signal induced by H2O2, but the lack of GPX4 would cause further deterioration of ER stress signal in the absence of SELS. In conclusion, maternal HMSeBA supplementation might alleviate ROS induced intestinal ER stress by improving the expression of SELS and GPX4 in their offspring. Thus, maternal HMSeBA supplementation might be benefit for the intestinal health of their offspring.